2010
DOI: 10.3988/jcn.2010.6.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase in Intrathoracic Pressure as a Contributing Factor to Cardioembolic Stroke

Abstract: BackgroundThe hemodynamic effects of increased intrathoracic pressure (ITP) have been the focus of many investigations. However, very little is known about the effects of elevated ITP on the occurrence of stroke.Case ReportFour young patients with a cardioembolic source of stroke were examined. In all cases the stroke was preceded by an increase in ITP that occurred during coughing, vomiting, or sexual intercourse.ConclusionsWe suggest that cardioembolic stroke is facilitated by situations in which ITP is elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…We also found that the application of mechanical ventilation and ECMO was related to both ischemic and hemorrhagic IOS. Positive pressure ventilation may provoke thromboembolism by inducing hypercoagulable state, opening unrecognized patent foramen ovale, and new-onset atrial fibrillation [15][16][17][18][19]. In addition, weaning from mechanical ventilation may induce hemodynamic changes and cardiac failure [20].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the application of mechanical ventilation and ECMO was related to both ischemic and hemorrhagic IOS. Positive pressure ventilation may provoke thromboembolism by inducing hypercoagulable state, opening unrecognized patent foramen ovale, and new-onset atrial fibrillation [15][16][17][18][19]. In addition, weaning from mechanical ventilation may induce hemodynamic changes and cardiac failure [20].…”
Section: Discussionmentioning
confidence: 99%
“…After screening, a total of 20 studies, which included 26 IS patients associated with sexual intercourse, were included. The clinical characteristics of previous studies on IS associated with sexual intercourse are summarized in Table 1 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The median (range) age was 34 (18-58) years, average age was 34.53 ± 10.08 years, and sex ratio was 1.6:1 (female:male = 16:10).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of abnormal venous-arterial channels, including patent foramen ovale (PFO), atrial septal defect (ASD), patent ductus arteriosus, and pulmonary arteriovenous malformations (PAVMs), is crucial for the occurrence of paradoxical embolization. Some studies have reported an association between paradoxical embolization related to PFO or ASD and sexual intercourse [6][7][8][9][10][11][12][13][14]. The plausible key process is the increase in the intrathoracic pressure during sexual intercourse, similar to during the Valsalva maneuver that facilitates or results in right-toleft shunting through the PFO or ASD.…”
Section: Etiologies and Mechanisms Of Is Associated With Sexual Inter...mentioning
confidence: 99%